Nisab Zakat Fitrah Dalam Pembelajaran Perbandingan Senilai - Yudi Yunika Putra; Adi Saputra (Jurnal Inovasi Matematika, 2020)
Mathematical Comparison theory is very important because students are often faced by comparative case in their daily life. Besides, the theory as well as implementation of zakat fitrah must be understood by moslems. Therefore, the the merging of these two concepts is a breakthrough in producing mathematics learning material. The purpose of this study was to produce the learning path in Mathematical comparison learning material by merging nisab theory of zakat fitrahThe method used in this study was design research that consisted of three steps namely introductory design (preparing for the experiment or preliminary design), try out (the design experiment), and retrospective analysis. Data were analyzed descriptively and retrospectively with HLT as the reference or guidance. The subjects in this study were the second semester students of the STKIP Muhamamdiyah Bangka Belitung Elementary School Teacher Education Study Program, with total number of 28 students. The criteria of selective the sample was that the the students were studying a basic mathematics concept course with Mathematical comparison as one of the materials. In this study, students were able to model their respective completion strategies and in accordance with the concept of worth comparison. HLT was designed to bring out students’ creativity in solving problems.